LEGAL ANALYSIS OF POST-DISASTERS LANDSLIDE MITIGATION POLICY IN BRUNO, PURWOREJO DISTRICT - Dewi, Indah Kusuma; Hardin, Hardin; Santoso, William Adi (NOMOI Law Review, 2025)
This study aims to analyze various obstacles faced in the implementation of post-landslide disaster mitigation in Bruno District, Purworejo Regency. Landslides are disasters that often occur in this area due to the hilly geographical conditions and are prone to landslides, so that they require fast, precise, and sustainable post-disaster handling. This research uses a normative-empirical legal method with a statute approach, case approach, historical approach, and also a sociological approach. The results of the study indicate that the landslide disaster mitigation policy implemented by the BPBD of Purworejo Regency in Bruno District has referred to the provisions of Law Number 24 of 2007 concerning Disaster Management. BPBD has implemented structural mitigation efforts (such as installing early warning systems and mapping vulnerable areas) and non-structural (such as disaster education and formation of volunteers) and there are five main categories of obstacles in the implementation of post-disaster mitigation, namely: institutional obstacles, regulations and planning, resources, socio-cultural, and technical and infrastructure obstacles. Weak coordination between agencies, limited budget and experts, and low community participation are dominant factors that hinder the effectiveness of post-disaster mitigation. Therefore, it is necessary to strengthen institutional capacity, prepare locally-based regulations, and actively involve the community as part of a sustainable mitigation strategy.